(untitled) (Nigerian Journal of Pharmaceutical Research, 2024)
Background: Naproxen has poor aqueous solubility and high permeability, making its formulation into oral dosage form challenging. The objective of this work was to enhance naproxen aqueous solubility by formulating it into solid dispersion (SD) using genetically modified cassava starch (GMCS) and hydroxypropyl methyl cellulose (HPMC) as polymers, and polysorbate-80 as surfactant. Materials and Methods: Naproxen SD was prepared by solvent evaporation. Different polymer-drug ratios (1:1, 2:1, 3:1 and 4:1) were used. The SDs were evaluated for solubility and the optimum formulation (S2) subjected to Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC) and scanning electron microscopy (SEM). Pure naproxen tablets (TN) and S2 tablets (T2) were directly compressed and assessed for hardness, friability, weight uniformity, disintegration and dissolution times. Results: The SD of polymer/drug ratio 2:1 and GMCS/HPMC proportion 2:1 had the highest solubility with the polymers showing synergism. Incorporating polysorbate-80 improved solubility by over 20 folds. SEM micrograph of the SD appeared smooth and spherical. DSC thermogram indicated a reduction in crystallinity of naproxen. FTIR spectrum showed no evidence of interaction with the polymers. T2 and TN tablets showed acceptable hardness, disintegration time and weight uniformity. The t50 and t90 dissolution values for T2 were 4.9 and 37.7 minutes respectively which were considerably lower than that of TN (28.57 and 63.42 minutes). Conclusion: Naproxen solubility was enhanced by solid dispersion formulation using genetically-modified cassava starch/HPMC blend. Synergistic effect in the improvement of naproxen solubility was established between the polymers. Inclusion of polysorbate-80 also improved naproxen solubility in the solid dispersion.